Assisting Kindergarten Teachers To Learn English Through Make A Match Model - Afriani, Rini; Sepdanius, Endang; Fithriah, Rahmuliani (UNIVERSITAS MUHAMMADIYAH MATARAM, 2025)
Mastery of English at an early age plays an important role in preparing the younger generation to face future challenges. In this case, teachers need assistance in order to provide learning that suits the needs of today's learners. This community service activity aims to improve the competence of kindergarten teachers in teaching English through the Make a Match model. The service partners in this activity are teachers from Kartika Kindergarten in Padang City, namely TK Kartika I-6, I-7, I-8, I-54, I-56, I-55, I-61, and I-63. The service method used is training and mentoring, where participants are given an understanding and direct practice related to the application of the Make a Match method in learning. The result of this service activity is that the teachers seemed very enthusiastic and eager to be involved in the implementation of the English learning model provided. Teachers seemed actively involved in improving English language skills. Teachers assessed that this model is effective in improving skills in English learning. The importance of the results of this service activity is the increased competence of kindergarten teachers in teaching English, which is expected to have a positive impact on the quality of learning in the classroom and the development of students' language skills.